2022
DOI: 10.1126/scitranslmed.adc9967
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cholesterol homeostasis in the living human brain

Abstract: Alterations in brain cholesterol homeostasis have been broadly implicated in neurological disorders. Notwithstanding the complexity by which cholesterol biology is governed in the mammalian brain, excess neuronal cholesterol is primarily eliminated by metabolic clearance via cytochrome P450 46A1 (CYP46A1). No methods are currently available for visualizing cholesterol metabolism in the living human brain; therefore, a noninvasive technology that quantitatively measures the extent of brain cholesterol metabolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 72 publications
1
10
0
Order By: Relevance
“…The finding of elevated cholesterol-derived oxysterols in females, despite stable overall cholesterol levels, suggests baseline cholesterol turnover may be increased in females. Our findings agree with recently published work [ 70 ] showing a significantly higher baseline brain cholesterol clearance via CYP46A1 in women than in age-matched men. The observed male vs. female difference in 8-DHC can be attributed to the action of the X-linked EBP enzyme, while the origins of the other differences are unknown at the current time.…”
Section: Discussionsupporting
confidence: 93%
“…The finding of elevated cholesterol-derived oxysterols in females, despite stable overall cholesterol levels, suggests baseline cholesterol turnover may be increased in females. Our findings agree with recently published work [ 70 ] showing a significantly higher baseline brain cholesterol clearance via CYP46A1 in women than in age-matched men. The observed male vs. female difference in 8-DHC can be attributed to the action of the X-linked EBP enzyme, while the origins of the other differences are unknown at the current time.…”
Section: Discussionsupporting
confidence: 93%
“…Our current work shows that gonadectomy leads to decreased Cyp46a1 expression in mice. Furthermore, a recent study has shown higher CYP46A1 levels in young, cognitively normal women in comparison to men, suggestive of a role for sex hormones in CYP46A1 regulation ( 72 ). Together, these findings encourage further investigation of the interplay between sex hormone levels, brain cholesterol turnover, and neurodegeneration in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Combined PET/CT studies and separate magnetic resonance imaging (MRI) studies were performed with two rhesus monkeys (male, 5.05–6.00 kg), as previously described. , After administering ketamine (10 mg/kg) via intramuscular injection for anesthesia, subjects were placed on the scanning bed in a supine position for brain T1-weighted MR anatomical images on a 3.0 T scanner (GE Discovery 750, Milwaukee). While MRI images were acquired without the need for inhalative anesthesia, PET studies required initial anesthesia with ketamine (10 mg/kg; i.m.…”
Section: Methodsmentioning
confidence: 99%